2003
DOI: 10.1002/chin.200341249
|View full text |Cite
|
Sign up to set email alerts
|

High‐Valent Iron and Manganese Complexes of Porphyrins and Related Macrocycles

Abstract: Organic chemistryOrganic chemistry Z 0200 High-Valent Iron and Manganese Complexes of Porphyrins and Related Macrocycles -[274 refs.]. -(WEISS, R.; GOLD, A.; TRAUTWEIN, A. X.; TERNER, J.; Porphyrin Handb. 4 (2000) 65-96; Lab. Cristallochim. Chim. Struct., CNRS, Inst. Le Bel, F-67070 Strasbourg, Fr.; Eng.) -Lindner 41-249

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The key reactive intermediates are postulated as high-valent iron–oxo porphyrin species defined in the biological context as cpd I (Fe IV (O)­(porphyrin •+ )), formally an Fe V (O) complex, and cpd II (Fe IV (O)­(porphyrin)). The terms “compound I” and “compound II” were historically applied to the reactive ferryl species found in horseradish peroxidases (HRP) but are now used to describe isoelectronic iron–oxo porphyrin species in other heme enzymes . Studies of synthetic high-valent iron–oxo porphyrin complexes have provided valuable insights into the reactivity of these species because of the relative ease of control of the ligand steric and electronic properties, as well as reaction environment, as compared to heme enzymes.…”
Section: Metal–oxo Porphyrinoid Complexes As Models For Biological Ox...mentioning
confidence: 99%
See 1 more Smart Citation
“…The key reactive intermediates are postulated as high-valent iron–oxo porphyrin species defined in the biological context as cpd I (Fe IV (O)­(porphyrin •+ )), formally an Fe V (O) complex, and cpd II (Fe IV (O)­(porphyrin)). The terms “compound I” and “compound II” were historically applied to the reactive ferryl species found in horseradish peroxidases (HRP) but are now used to describe isoelectronic iron–oxo porphyrin species in other heme enzymes . Studies of synthetic high-valent iron–oxo porphyrin complexes have provided valuable insights into the reactivity of these species because of the relative ease of control of the ligand steric and electronic properties, as well as reaction environment, as compared to heme enzymes.…”
Section: Metal–oxo Porphyrinoid Complexes As Models For Biological Ox...mentioning
confidence: 99%
“…Excellent reviews on the reactivity of iron–oxo porphyrin complexes can be found in the literature, including those from Fujii (2000, 2002, and 2016) Meunier et al (2004), Groves (2006), Newcomb et al (2006), Nam (2007), Costas (2011), Ray and Meyer (2012), and Rutkowska-Zbik et al (2014) . Dedicated chapters in The Porphyrin Handbook (2000) , ,− Handbook of Porphyrin Science , and other compilations can also be found. This section will focus on recently published works in this area.…”
Section: Metal–oxo Porphyrinoid Complexes As Models For Biological Ox...mentioning
confidence: 99%
“…The porphyrin-π-cation radical in model complexes has a characteristic UV-visible spectrum with the Soret band between 390 – 406 nm, and a weak band between 670 – 690 nm [149] which appear in CPO at about 370 nm and 690 nm, respectively [150]. In general, the most characteristic feature of Cpd I is the broad weak band at 650 – 690 nm in absorption spectra (ε = 4 – 12 mM -1 cm -1 ), which is indicative of the porphyrin radical [151].…”
Section: The Compound I and Compound Ii Ferryl-oxo Speciesmentioning
confidence: 99%
“…Resonance Raman studies show that the Fe=O stretch vibration frequency for six-coordinated porphyrin model complexes with non-radical character of the porphyrin (Compound II) appears between 818 cm -1 and 841 cm -1 [163]. If the porphyrin is a pi-cation radical (Compound I) this frequency shifts to lower values at about 760–780 cm -1 [149]. …”
Section: The Compound I and Compound Ii Ferryl-oxo Speciesmentioning
confidence: 99%
See 1 more Smart Citation